2020
DOI: 10.1038/s41598-020-72012-8
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of fat-derived CD73 positive cells from multiple human tissues, prospective isolated mesenchymal stromal cells

Abstract: Somatic stem cells have been isolated from multiple human tissues for their potential usefulness in cell therapy. Currently, mesenchymal stromal cells (MSCs) are prepared after several passages requiring a few months of cell culture. In this study, we used a prospective isolation method of somatic stem cells from gestational or fat tissues, which were identified using CD73 antibody. CD73-positive population from various tissues existed individually in flowcytometric pattern, especially subcutaneous fat- and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…We then characterized the phenotype of hASCs via fluorescenceactivated cell sorting analysis in accordance with the low expression of surface makers including CD14, CD34, and CD45 and high expression of major surface marker including CD73 and CD105. [53][54][55][56] As predicted, high expression of CD73 and CD105 and low expression of CD14, CD34, and CD45 were observed (Figure S3), consistent with that in prior studies. 53,57,58 To observe cell viability and the adhesion pattern of hASCs grown on a culture plate, PDMS, and IA-PDMS, the Live/Dead assay was used.…”
Section: Characterization Of Human Adipose-derived Stem Cells and Inv...supporting
confidence: 91%
“…We then characterized the phenotype of hASCs via fluorescenceactivated cell sorting analysis in accordance with the low expression of surface makers including CD14, CD34, and CD45 and high expression of major surface marker including CD73 and CD105. [53][54][55][56] As predicted, high expression of CD73 and CD105 and low expression of CD14, CD34, and CD45 were observed (Figure S3), consistent with that in prior studies. 53,57,58 To observe cell viability and the adhesion pattern of hASCs grown on a culture plate, PDMS, and IA-PDMS, the Live/Dead assay was used.…”
Section: Characterization Of Human Adipose-derived Stem Cells and Inv...supporting
confidence: 91%
“…However, CD73 expression on MSC has been associated with their anti-inflammatory effects and reparative properties [ 28 ], and on unpassaged subcutaneous adipose tissue MSC, the expression of CD73 gave a higher proliferative capacity and increased stem cell marker expression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 24, 2022. ; https://doi.org/10. 1101/2022 We previously demonstrated that cluster of differentiation (CD)73 molecules can be used to efficiently isolate cell populations with MSC characteristics from human and rodent adipose tissues (Suto et al, 2017;Suto et al, 2020). However, the specific characteristics of CD73 + cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%